Down-Regulating Cucumber Sucrose Synthase 4 (CsSUS4) Suppresses the Growth and Development of Flowers and Fruits. (24th December 2018) - Fan, Jingwei; Wang, Hongyun; Li, Xiang; Sui, Xiaolei; Zhang, Zhenxian
Abstract: Sucrose synthase (SUS), which catalyzes the reversible conversion of sucrose and uridine diphosphate (UDP) into fructose and UDP-glucose, is a key enzyme in sucrose metabolism in higher plants. In this study, we used reverse genetic approaches and carbohydrate analysis to investigate the role of cucumber sucrose synthase gene 4 ( CsSUS4 ) in the growth and development of sink organs. Transcript analyses showed that CsSUS4 was predominantly expressed in sink organs, particularly in flowers, fruits and roots, and that CsSUS4 protein was localized to companion cells and phloem parenchyma cells. Down-regulation of CsSUS4 expression resulted in a decrease in SUS activity in conjunction with lower hexose, starch and cellulose contents in fruits, and led to an overall reduction in the size and weight of flowers and fruits. Furthermore, CsSUS4 overexpression (OE) lines exhibited increased carbohydrate content, and larger and heavier flowers and fruits. The numbers of multi-petal flowers and multi-carpel fruits were greater in CsSUS4 -OE plants compared with wild type and were regulated by MADS-box transcription factor. These results demonstrate that CsSUS4 plays important roles in the growth and development of cucumber flowers and fruits.